2008
DOI: 10.1101/sqb.2008.73.031
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Normal Hematopoietic and Leukemia Stem Cell Hierarchy

Abstract: Many types of adult tissues, especially for high turnover tissues such as the blood and intestinal system, stand on a hierarchical tissue-specific stem cell system. Tissue-specific stem cells concurrently have self-renewal capacity and potential to give rise to all types of mature cells in their tissue. The differentiation process of the tissue-specific stem cell is successive restriction of these capacities. The first progeny of tissue-specific stem cells are multipotent progenitors (MPPs) that lose long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 99 publications
3
109
0
1
Order By: Relevance
“…There are many precedents for progenitor cell populations in other organisms that contain numerous cell types with different properties or lineage potential (Spangrude et al, 1988;Chao et al, 2008;Biressi and Rando, 2010). Furthermore, blastema cells in amphibians were long considered to be a multipotent progenitor type, but it is now known that there is lineage restriction in the cells of the blastema in Xenopus and axolotl, as well as in zebrafish (Gargioli and Slack, 2004;Kragl et al, 2009;Knopf et al, 2011;Tanaka and Reddien, 2011;Tu and Johnson, 2011).…”
Section: The Specialized Neoblast Modelmentioning
confidence: 99%
“…There are many precedents for progenitor cell populations in other organisms that contain numerous cell types with different properties or lineage potential (Spangrude et al, 1988;Chao et al, 2008;Biressi and Rando, 2010). Furthermore, blastema cells in amphibians were long considered to be a multipotent progenitor type, but it is now known that there is lineage restriction in the cells of the blastema in Xenopus and axolotl, as well as in zebrafish (Gargioli and Slack, 2004;Kragl et al, 2009;Knopf et al, 2011;Tanaka and Reddien, 2011;Tu and Johnson, 2011).…”
Section: The Specialized Neoblast Modelmentioning
confidence: 99%
“…These cells eventually differentiate into lineagerestricted common lymphoid progenitors (CLPs) and common myeloid progenitors (CMPs), which are committed to terminal differentiation and unable to selfrenew (Chao et al 2008). Previous studies have demonstrated that oncogenic Kras drives proliferation and differentiation of HSCs and myeloid progenitors, but does not promote-and, in fact, depends on-self-renewal capabilities to initiate disease (Sabnis et al 2009;Zhang et al 2009).…”
Section: Krasmentioning
confidence: 99%
“…Similar to hematopoietic stem cells (HSCs) in normal blood development, LSCs can give rise to the entire cellular hierarchy and sustain leukemia expansion through an unlimited self-renewal capability. 1 This model is supported by studies in which LSC-enriched cell populations, such as the CD34 ϩ CD38 Ϫ leukemic cells in human acute myeloid leukemia (AML), transplanted into SCID mice are able to fully recapitulate the process of leukemia development. 2,3 LSCs can be derived from different cellular compartments according to the leukemia type and disease stage.…”
Section: Introductionmentioning
confidence: 99%